Interventions on Sexuality for Adolescents with Autism Spectrum Disorder: A Systematic Review. - Picard-Pageau, William; Morales, Ernesto (Sexuality & Disability, 2022)
Sexuality and intimate relationships are topics of interest to adolescents and young adults with Autism Spectrum Disorder (ASD). Given their relative difficulties to the social dimension, several intervention programs have been developed to meet this demand, but the complexity of the reality experienced by these young people limits the effectiveness of these intervention programs. To find the effects of different intervention programs to influence the development of sexuality and sexual health of adolescents with ASD and determine the impact of these interventions on the parents, through a systematic review. Literature review conducted on November 27, 2019 in the psycINFO, Pubmed, web of science and CINAHL databases. Intervention programs consisting solely of teaching sessions improve the knowledge of the youth. However, when they also included a direct approach or homework, behavioral effects were also observable. Parent-focused intervention programs resulted in a slight increase in parents' comfort level and ability to interact well with their youth. Intervention programs targeting school-based workers appear to have a limited effect, having good concrete results with youth for some workers and no results for others, while intervention programs targeting health professionals have no conclusive results. The results of the literature review are not very transferable to practice because of the low level of evidence in the articles included, however, they offer an interesting starting point. Further research is needed to equip health professionals to intervene in sexuality after youth with ASD.